Integrated metagenomics and metabolomics analysis reveals dynamic changes of microbiota and metabolic profile during fermentation of cigar tobacco (Nicotiana tabacum L.) leaves - Yang, Ting; Lin, Xiaolu; Chen, Rui; Wang, Ruiqi; Li, Tong; Shen, Fulong; Zhang, Xiaowei; Lai, Lianghua; Lu, Bing; Wei, Jiliang; Xie, Xiaofang (Frontiers in Genetics, 2025)
Optimizing fermentation duration is critical for producing high-quality cigar tobacco leaves This study examines changes in microorganisms and metabolites during CTL fermentation at four time points: 0 days (T0), 25 days (T1), 50 days (T2), and 75 days (T3). We observed a decreasing trend in total soluble sugars, starch, total nitrogen, and nicotine levels as fermentation progressed. Notably, chemical components stabilized after T2 stages. The microbial community showed dynamic fluctuations, with alpha diversity indices (Shannon, ACE, Pielou’s evenness, and Chao-2) reaching equilibrium at T2 and maintaining stability thereafter. Dominant genera such as Staphylococcus, Aspergillus, Sphingomonas, and Penicillium persisted throughout the fermentation process. A total of 1801 metabolites were identified, with 584 showing differential expression across the fermentation periods. Notably, comparisons between T0 and T1, T2, and T3 revealed 218, 377, and 419 differentially expressed metabolites, respectively. KEGG enrichment analysis identified 28 co-existing metabolic pathways, seven of which are linked to cigar quality formation. Furthermore, 29 out of 47 differential metabolites significantly correlated with the eight dominant microbial genera. These findings indicate that the T2 stage achieves optimal balance between microbial activity and metabolite stabilization, providing a scientific basis for industrial process optimization.